Taurine supplementation improves liver glucose control in normal protein and malnourished mice fed a high‐fat diet. Issue 3 (26th December 2012) - Batista, Thiago M.; Ribeiro, Rosane A.; da Silva, Priscilla M. R.; Camargo, Rafael L.; Lollo, Pablo C. B.; Boschero, Antonio C.; Carneiro, Everardo M.
<x xml:space="preserve">Abstract</x> Scope Poor nutrition during the perinatal period is associated with an increased risk for metabolic syndrome in adulthood. Taurine (TAU) regulates β‐cell function and glucose homeo‐stasis. Here, we assessed the effects of TAU supplementation upon adiposity and glucose control in malnourished mice fed a high‐fat diet (HFD). Methods and results Weaned male C57BL/6J mice were fed a control (14% protein ‐ C) or a protein‐restricted (6% protein ‐ R) diet for 6 weeks. Afterwards, mice received or not an HFD for 8 weeks (CH and RH). Half of the HFDmice were supplemented with 5% TAU after weaning (CHT and RHT). Protein restriction led to typical malnutrition features. HFD increased body weight, adiposity, and led to hyperleptinemia, hyperphagia, glucose intolerance, and higher liver glucose output in RH and CH groups. Fasted R mice showed higher plasma adiponectin levels and increased phosphorylation of the AMP‐activated protein kinase (p‐AMPK) in the liver. These parameters were reduced in RH mice and increased p‐AMPK persisted in RHT. TAU prevented obesity and improved glucose tolerance only in CHT, but liver glucose control was ameliorated in both supplemented groups. Better CHT liver glucose control was linked to increased Akt (thymoma viral proto‐oncogene/protein kinase B) phosphorylation. Conclusion Malnourished mice fed an HFD developed obesity, glucose intolerance, and increased liver glucose output. TAU preserved only normal liver glucose control in RHT mice, an effect associated with increased liver p‐AMPK content.